Pengaruh Aditif MEA terhadap Sifat Listrik Lapisan Tipis - Sefriyani, Sefriyani; Sanjaya, Hary; Budiman, Septian (Lembaga Yasin AlSys, 2024)
This research discusses the effect of adding MEA additives on the synthesis of CuSnO3 thin films using the dipcoating method. This type of research uses experimental.. Based on UV-DRS analysis, the optimum bandgap data was obtained at 1.8034 eV. The addition of additives greatly influenced the reduction of the bandgap. With FPP, a good resistance of 38.59 Ω was obtained at 6x immersion, with a resistivity of 0.000330 Ωm with a conductivity value of 3030.30 Ω-1m-1. From the resulting data it can be concluded that the thicker the layer, the lower the resistance value, and the lower the resistivity, the better the electrical conductivity.